Analisis Pengaruh Pertumbuhan Penjualan, Struktur Aset, dan Profitabilitas terhadap Struktur Modal - Miswanto Miswanto; Aditia Yusuf Setiawan; Aprih Santoso (Jurnal Maksipreneur, 2022)
The purpose of this study is to examine the effect of sales growth, asset structure, and profitability on the company's capital structure. The sample used was 119 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2012 to 2015. The determination of the sample data in this study used a purposive sampling method, while the data used were panel data. The findings in this study indicate that sales growth and asset structure have a significant and positive effect on capital structure. On the other hand, profitability has a significant and negative effect on capital structure. With these findings, this study supports the results of previous research and shows that theories to explain the capital structure and the factors that influence it are not mutually exclusive.